An Analysis of Factors of Culture Shock and Culture Shock Stages Occurred in the Main Character of She Smells of Turmeric Novel - Syifa Aisyah Likandi; Arie Sugiyartati (JEdu: Journal of English Education, 2023)
Culture shock occurs because of the culture gap and differences, such as habit, behaviour, values, religion, tradition, and other cultural aspects. The symptoms of a sojourner who fights the shock are explained by the factors of culture shock and how they combat the cultural changes that are causing the shock which described in four stages. This study aims to elucidate the existence factor of culture shock and the stage of culture shock that corresponds to the protagonist of the novel "She Who Smells Turmeric". This study is an application of the culture shock stage theory carried out by Karvelo Oberg in 1960. Researcher used romances as data sources and scenes from novels as the data. The research method is a descriptive qualitative method. Researchers collected data by repeatedly reading the novel and highlighting scenes that could be considered as data. The researcher applied interactive analysis, which he performed three steps such as data reduction, data display, and data inference. As a result of collecting and analysing the data, the researchers found 26 data found as features of the culture shock phenomenon and 84 data found as four features to explain the factors that referred to CeCe as a guest who fought culture shock in Jakarta. We found 110 data consisting of data. Culture shocks CeCe after graduating from Los Angeles.